Las trabajadoras de Medellín : entre la necesidad y la exclusión (1850-1900) (2007)
ABSTRACT: This article presents some of the circumstances that influenced women s work in the popular sectors in Medellín, throughout the 2nd half of the nineteenth century. Using the documentation deposited in the Archivo Judicial de Medellín, the dispositions of the Cabildo de Medellín, and the discourse spread through the press, it exposes that the role assigned to women was dependant on an ideal of domesticity, caution and obedience to man. However, those who belonged to the popular classes had to perform multiple strategies as a means of survival for themselves and those who were dependant on them. It also examines the existing concepts regarding women and the paid labor done by them, as well as the specific shapes of this labor experience starting from some of the most widely registered in the consulted documentation. An ideology of exclusion of the female gender, manifested in the hierarchical order of society, determined certain asymmetric power relations between the sexes, specially materialized in the poverty of women.